2014
DOI: 10.1007/s11033-014-3424-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Methylenetetrahydrofolate reductase maternal gene in Down syndrome: increased susceptibility in women carriers of the MTHFR 677T allele

Abstract: Because a number of data studies include some controversial results about Methylenetetrahydrofolate reductase (MTHFR) polymorphisms and Down syndrome (DS), we performed a meta-analysis to determine a more precise estimation of this association. Studies were searched on PubMed, EMBASE and Lilacs-Scielo, up to April 2013, and they were eligible if they included case mothers (DSM) that have gave birth to children with DS, and controls mothers (CM) that have gave birth to healthy children without chromosomal abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 61 publications
3
18
0
2
Order By: Relevance
“…28---30 The results regarding the contribution of these polymorphisms to the etiology of TS are conflicting, as the C677T SNP was associated with TS in one study, 28 whereas in the others it was A1298C. 47 The genetic polymorphisms analyzed here seem to influence the severity of the clinical manifestations of TS, as well as response to treatment. 47 The genetic polymorphisms analyzed here seem to influence the severity of the clinical manifestations of TS, as well as response to treatment.…”
Section: Chromosomal Nondisjunctionmentioning
confidence: 91%
“…28---30 The results regarding the contribution of these polymorphisms to the etiology of TS are conflicting, as the C677T SNP was associated with TS in one study, 28 whereas in the others it was A1298C. 47 The genetic polymorphisms analyzed here seem to influence the severity of the clinical manifestations of TS, as well as response to treatment. 47 The genetic polymorphisms analyzed here seem to influence the severity of the clinical manifestations of TS, as well as response to treatment.…”
Section: Chromosomal Nondisjunctionmentioning
confidence: 91%
“…It was reported initially [17] in the year 1999, that increased plasma hcy level and an increased frequency of both MTHFR 677CT and TT genotypes among the mothers of DS individuals are strongly linked and since then this polymorphism has been tested in more than 30 case-control studies across the globe and confirmed this association with very few exceptions. As far as published literatures are concerned five large meta-analyses have been done till date between the year 2013 and 2014 to address this issue [18][19][20][21][22], with the latest one that includes data from 34 case-control studies for a total of 3.098 women having DS child and 4.852 control mothers [21]. The outcome of all these meta-analyses suggest that the overall risk as represented by odds ratio (OR), for the birth of a child with Trisomy21 to the women who are carriers of the 677 T allele ranges from 1.2 to 1.5 according to the various genetic models under investigation, i.e., allele contrast, dominant, recessive, co-dominant, etc.…”
Section: Methylenetetrahydrofolate Reductase (Mthfr)mentioning
confidence: 99%
“…The outcome of all these meta-analyses suggest that the overall risk as represented by odds ratio (OR), for the birth of a child with Trisomy21 to the women who are carriers of the 677 T allele ranges from 1.2 to 1.5 according to the various genetic models under investigation, i.e., allele contrast, dominant, recessive, co-dominant, etc. Subsequent data stratification into ethnic groups revealed that the risk is higher in Asians (OR = 1.5), and lower in Caucasians and/or other groups (OR usually ranging between 1.0 and 1.4) [19,20,22]. The meta-analyses performed by Wu et al [19]; Yang et al [20]; Rai et al [21]; Victorino et al [22] revealed that the frequency of the MTHFR 677 T allele is higher in Caucasian mother of DS child (ranging from 35.6 to 41.5%), followed by Brazilians (ranging from 33.5 to 33.9%), and lower in Asian populations (ranging from 20.0 to 32.3%).…”
Section: Methylenetetrahydrofolate Reductase (Mthfr)mentioning
confidence: 99%
See 2 more Smart Citations